2020
DOI: 10.3390/ijms21072393
|View full text |Cite
|
Sign up to set email alerts
|

Calebin A Potentiates the Effect of 5-FU and TNF-β (Lymphotoxin α) against Human Colorectal Cancer Cells: Potential Role of NF-κB

Abstract: Objective: The majority of chemotherapeutic agents stimulate NF-κB signaling that mediates cell survival, proliferation and metastasis. The natural turmeric non-curcuminoid derivate Calebin A has been shown to suppress cell growth, invasion and colony formation in colorectal cancer cells (CRC) by suppression of NF-κB signaling. Therefore, we hypothesized here that Calebin A might chemosensitize the TNF-β-treated tumor cells and potentiates the effect of 5-Fluorouracil (5-FU) in advanced CRC. Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 77 publications
7
39
0
Order By: Relevance
“…In addition, these specific anti-tumor actions of Calebin A further correlated with inhibition of cell metastatic (CXCR4, MMP-9) and proliferative (cyclin D1) biomarkers, all of which are known to have a NF-κB binding site in their promoters, thus promoting their transcription. These results are consistent with our previous reports with various other natural products such as turmeric [25,40,75] and resveratrol [26,27,76,77]. Moreover, Calebin A, similar to BMS-345541, reduced the multicellular pro-inflammatory TME-stimulated phosphorylation and translocation of the p65 subunit of NF-κB from the cytoplasm to the nucleus, suggesting that Calebin A, which possesses pro-apoptotic properties, has the potential to prevent tumor invasion and proliferation, at least in part, by up-stream targeting the IKK-NF-κB signaling pathway.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In addition, these specific anti-tumor actions of Calebin A further correlated with inhibition of cell metastatic (CXCR4, MMP-9) and proliferative (cyclin D1) biomarkers, all of which are known to have a NF-κB binding site in their promoters, thus promoting their transcription. These results are consistent with our previous reports with various other natural products such as turmeric [25,40,75] and resveratrol [26,27,76,77]. Moreover, Calebin A, similar to BMS-345541, reduced the multicellular pro-inflammatory TME-stimulated phosphorylation and translocation of the p65 subunit of NF-κB from the cytoplasm to the nucleus, suggesting that Calebin A, which possesses pro-apoptotic properties, has the potential to prevent tumor invasion and proliferation, at least in part, by up-stream targeting the IKK-NF-κB signaling pathway.…”
Section: Discussionsupporting
confidence: 94%
“…Biomedicines 2020, 8, x FOR PEER REVIEW 3 of 17 progression in CRC [25,40]. Calebin A suppressed not only pro-inflammatory cytokine TNF-βinduced NF-B pathway activation, inhibiting proliferation, migration, and stimulated apoptosis in CRC cells [25,40], but also chemosensitized the CRC cells further towards 5-fluorouracil [40].…”
Section: Experimental Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the underlying role of molecular TNF-β and resveratrol signal transduction during tumorigenesis is still not fully understood. In fact, recent studies from our laboratory showed that TNF-β signaling induces NF-κB activation, colony formation, epithelium-to-mesenchymal transition, CSCs formation and migration of CRC tumor cells in a tumor microenvironment [ 18 , 42 , 85 ]. We found that resveratrol inhibits the expression and activation of TNF-β and TNF-β-promoted inflammatory microenvironments on the survival and malignancy of colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%